The Influence of Human Resource Competence and Utilization of Information Technology on the Quality of Financial Reports with Internal Control System as a Moderating Variable - Laka, Marta Dea Lu Mapa Wasa; Asyik, Nur Fadjrih; Mildawati, Titik (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study determines, examines, and analyzes internal control in moderating the utilization of information technology on financial statements quality at Perumda Wair Puan, Kabupaten Sikka. Furthermore, the research applies quantitatively with a causal approach. Independent variables were variables affected. Meanwhile, a dependent variable is a variable that is affected. The population to be studied in this research consists of the employees at the Perumda Wair Puan Office in Sikka Regency, totalling 114 individuals. The sampling was conducted through purposive sampling, focusing on civil servants in the accounting or finance department working at the Perumda Wair Puan Office in Sikka Regency. The number of respondents determined was 68 people out of 114. The data collection technique used purposive sampling. The data analysis technique used descriUITve statistics with MRA software. The result indicates that as follows (1) human resources competence has a negative effect on financial statements quality, (2) utilization of information technology has a negative effect on financial statements quality, (3) internal control systems strengthen the relationship between human resources competence and utilization of information technology on financial statements quality.